2004
DOI: 10.1038/sj.bmt.1704749
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening neurological complications after bone marrow transplantation in children

Abstract: Summary:Neurological complications may occur in BMT recipients (11-59%), frequently contributing to morbidity or mortality. They are the main causes of death in 10-15%. Lifethreatening neurological complications were seen in 11 out of 113 (9.7%) children who underwent BMT from HLAmatched family (n ¼ 7) or mismatched donors (n ¼ 4) at our institution. Diagnoses of patients with neurological complications were acute myeloblastic leukemia (AML) (five), thalassemia major (two), Fanconi anemia (two), Omenn syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 13 publications
11
89
2
Order By: Relevance
“…Chinese also came up with a similar result and also noticed a lower incidence of chronic GVHD in cord blood donor transplant compare to unrelated donor and with a similar outcome with a suitable sibling [38]. Post-HCT toxicity is a cause of concern in most transplant centers and is highlighted in various studies [39]. In our cohort,three patients acquired CMV infection after transplant and no one developed VOD, Haemorrhagic cystitis or other major complications, which could be the due to optimally matched donors and a good post HCT nursing support [40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 54%
“…Chinese also came up with a similar result and also noticed a lower incidence of chronic GVHD in cord blood donor transplant compare to unrelated donor and with a similar outcome with a suitable sibling [38]. Post-HCT toxicity is a cause of concern in most transplant centers and is highlighted in various studies [39]. In our cohort,three patients acquired CMV infection after transplant and no one developed VOD, Haemorrhagic cystitis or other major complications, which could be the due to optimally matched donors and a good post HCT nursing support [40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 54%
“…These findings are in accordance with previous clinical studies, which showed that neurological complications are seen more frequently in allogeneic, especially mismatched, transplantations 3,4 particularly in patients with grade II-IV GvHD. 2 However, there is a marked variability of incidence rate among the different published studies, ranging from 11% in clinical series up to 90% in autopsy studies. Only a few studies were undertaken in the paediatric age group.…”
Section: Discussionmentioning
confidence: 99%
“…5 Mismatched related or unrelated donor allogeneic transplantation and the occurrence of GvHD were the most significant risk factors for development of neurological complications, most probably related to pronounced immunosuppression in such patients. [2][3][4] The wide range of incidence rate of neurological symptoms reported in the previous studies may be in part attributable to different classifications used, heterogeneous study populations, risk profiles and follow-up periods. Therefore, comparability among these studies is limited and very few data are available in the paediatric population.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[9][10][11] The reported frequency and type of complications varies depending on case ascertainment definition and population examined. [12][13][14][15] In most studies, participants receiving allogeneic HCT are reported to have a higher risk of neurological complications compared to autologous HCT participants. However, one large retrospective study found the incidence similar but the frequency and distribution of complications varied.…”
Section: Hematopoietic Cell Transplantation: General Overviewmentioning
confidence: 99%